Massive spontaneous haemorrhage in a plexiform neurofibroma: A case report and discussion of the literature. (October 2020) - Miller, Jamie; Perotti, Vanessa; Moore, Paige
Highlights: Haemorrhage occurring in plexiform neurofibromas are a rare clinical entity, and may be fatal. There is a lack of consensus in the literature regarding management, owing to low incidence. We outline the presentation and management of a large spontaneous haemorrhage in a middle aged patient. The available literature is discussed. Abstract: Neurofibromatosis Type 1 (NF1) is a neurocutaneous tumour syndrome characterised by mutations in the NF1 gene and resultant neurofibromin protein. The condition is associated with several stigmata of variable penetrance, including various tumours. Massive and fatal haemorrhage arising from plexiform neurofibromas has been described in NF1 patients, though it is a rare clinical entity. The aetiology of massive haemorrhage in NF1 patients appears to be related to vasculopathy, including aneurysms and pseudoaneurysms, often arising within plexiform neurofibromas. There is currently no evidence-based consensus for managing this rare clinical emergency, likely as a result of its low incidence. We describe a case of massive haemorrhage in an NF1 patient managed via embolisation and discuss the literature.